(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This exploratory article examines the multifaceted process of developing bilingual terminological competence in Uzbek and Russian among medical students in Uzbekistan. Grounded in an analysis of contemporary research and drawing upon pedagogical observations, the paper highlights the unique sociolinguistic context where Russian historically holds a significant position in medical education and literature, while Uzbek is increasingly vital as the state language and for direct patient communication. Key challenges are identified, including linguistic interference, the ongoing standardization of Uzbek medical terminology, and the need for didactic materials that adequately reflect bilingual clinical realities. The article explores various pedagogical strategies, such as comparative terminological analysis, case-based learning, and the integration of authentic communicative tasks. Furthermore, it presents observations on student learning patterns and discusses the crucial implications of robust bilingual terminological proficiency for effective healthcare delivery, patient trust, and the overall enhancement of medical education standards in Uzbekistan. The discussion underscores the necessity for continued research, curriculum innovation, and resource development to support this essential competence.